Navodila avtorjem prispevkov za časopis Informatica Medica Slovenica (slovenska oblika) - Vidmar, Gaj (Informatica Medica Slovenica, 2015)
The paper provides detailed technical instructions and brief substantial guidelines to the prospective authors. The title should be informative but not too long. It can include a rhetorical question, allusion or wordplay, but only if carefully considered. The top title should be typeset in the IMS Paper Title Top style and the bottom one in the IMS Paper Title Bottom style. If the paper itself is not written in English, the top title should be in the language of the paper and the bottom title and abstract should be in English. If the paper is in English, the bottom title and abstract should be in Slovenian. British spelling should be used for the English text. The abstract should not exceed 250 words. It should be typeset in the IMS Abstract style. It should not have subtitles, sections or be divided into paragraphs. For an empirically oriented paper, the structure of the abstract should follow the structure of the paper (background, methods, results, conclusions); a non-empirical paper gives more freedom to the authors regarding the structure of the abstract. The footnote of the title page should list the authors' institutions (in the language of the paper) and provide contact information (name, address and e-mail of the corresponding author).